PENGONTROLAN VPS (VIRTUAL PRIVATE SERVER) SEBAGAI SERVER RADIO STREAMING VIA ANDROID - Hidayat, Rohmat; Sutanta, Edhy; Raharjo, Suwanto (Jurnal Jarkom, 2014)
ABSTRACTRadio streaming is a technology for multimedia services are growing rapidly and become a trend at the moment is real-time multimedia, interactive and holding a very important role in todays society as a medium which is very actual for entertainment, information or business. Radio streaming service on computer networks generally involve a multipoint communication over the two sides simultaneously (server and client), which skipped on a TCP/IP network.On this research will be implemented a streaming server radio built on a VPS (virtual private server) namely a technology side about server operating systems and software that allows a machine with large capacity divided into several virtual machines. Every virtual machine serving the operating system and software independently and with new configuration that fast. With the technology advancement is very fast currently it is possible to develop a remote desktop application of a smartphone to a virtual machine.The trial was done in accordance with the principle of radio stream, where as the purpose of the research is how to develop the application as a streaming radio server control by leveraging advances in technology of mobile devices both smartphone or Android-based tablet PC anywhere so long as connected to the internet network. Give the admin a streaming radio the ease in doing his job without having to always carry a laptop or even a PC computer to do broadcasting a radio stream.Keywords: android, streaming radio, server, smartphone.